Enhancing Nitrate Ion Removal from Water using Fixed Bed Columns with Composite Chitosan-based Beads - Jamka, Zainab N.; Mohammed, Wadood T.; YOU, Zhenjiang; Abid, Hussein Rasool (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Water contamination is a pressing global concern, especially regarding the presence of nitrate ions. This research focuses on addressing this issue by developing an effective adsorbent for removing nitrate ions from aqueous solutions. two adsorbents Chitosan-Zeolite-Zirconium (Cs-Ze-Zr composite beads and Chitosan-Bentonite-Zirconium Cs-Bn-Zr composite beads were prepared. The study involved continuous experimentation using a fixed bed column with varying bed heights (1.5 and 3 cm) and inlet flow rates (1 and 3 ml/min). The results showed that the breakthrough time increased with higher bed heights for both Cs-Ze-Zr and Cs-Bn-Zr composite beads. Conversely, an increase in flow rate led to a decrease in breakthrough time. Notably, Cs-Ze-Zr and Cs-Bn-Zr demonstrated impressive removal efficiencies, reaching 87.23% and 92.02%, respectively. The optimal conditions for peak performance were found to be an inlet flow rate of 1 ml/min, a bed height of 3 cm, and initial concentrations of 400 mg/L and 600 mg/L for Cs-Ze-Zr and Cs-Bn-Zr, respectively.